2003
DOI: 10.1248/bpb.26.79
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Pharmacokinetics of Baicalein, Wogonin and Their Glycosides after Oral Administration of Scutellariae Radix in Humans.

Abstract: Baicalin, baicalein, wogonoside and wogonin are flavone constituents of Scutellariae Radix with various beneficial biological activities. The purpose of this study was to investigate the urinary pharmacokinetics of these flavones after oral administration of Scutellariae Radix commercial powder. Ten healthy male volunteers received a dose of 5.2 g commercial powder (comparable to 9 g crude drug), respectively. The concentrations of baicalin, baicalein and wogonin in the commercial powder as well as their metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(91 citation statements)
references
References 19 publications
7
82
0
2
Order By: Relevance
“…For example, Akao et al (24) and our previous study using a rat intestinal perfusion model demonstrated the secretion of BG in the intestine. Kidney disposition of conjugates of Ba was also reported (25). Therefore, it is probable that different organs may show their preference to the uptake of conjugates, and the preference may also vary with different plasma concentrations of the conjugates.…”
Section: −1mentioning
confidence: 89%
“…For example, Akao et al (24) and our previous study using a rat intestinal perfusion model demonstrated the secretion of BG in the intestine. Kidney disposition of conjugates of Ba was also reported (25). Therefore, it is probable that different organs may show their preference to the uptake of conjugates, and the preference may also vary with different plasma concentrations of the conjugates.…”
Section: −1mentioning
confidence: 89%
“…A recent study reported the urinary pharmacokinetics of wogonin after oral administration of a commercial powder of Scutellariae radix to humans (31). No free form of wogonin was found in the urine and the total excreted wogonin conjugates amounted to 11.6% of the administered dose.…”
Section: Pharmacokinetic Studiesmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] To our knowledge, two studies have reported the simultaneous determination of the bioactive flavonoids of Scutellariae Radix including all of baicalein, baicalin, wogonin, and wogonoside in biological samples with full validation data by using LC-MS/MS. 14,15 However, in those studies, the analytical method was validated in the restricted concentration ranges.…”
Section: Introductionmentioning
confidence: 99%